# please answer my question.....

Attachments:

## Answers

Answered by

1

**Hii****.****.**

**Answer**** ****is**** in**** ****att****achment****.**

**Hope ****this**** helps**** ****!**

Attachments:

Anonymous:
:)

Answered by

2

__GIVEN__

P(x) = ax^3 + x^2 - 2x + 4a - 9

g(x) = x + 1

g(x) is a factor of p(x)

** TO FIND** :- The value of a

__S____O____L____U____T____I____O____N__

According to **Factor Theorem**

__I____f x + 1 is a factor of p(x) then if we substitute its zero in p(x) the resultant value of p(x) will be equal to zero.__

x + 1 = 0

=> x = -1

Now if we put x = -1 in p(x) then the resultant value of the polynomial will be zero.

p(x) = ax^3 + x^2 - 2x + 4a - 9

p( - 1) = a (-1)^3 + (-1)^2 - 2 (-1) + 4a -9 =0

- a + 1 + 2 + 4a - 9 = 0

=> 3a - 6 = 0

=> a - 2 = 0

=> a = 2

__HENCE THE VALUE OF a is 2__

Similar questions

Science,
5 days ago

Biology,
5 days ago

Computer Science,
10 days ago

Math,
10 days ago

Science,
1 month ago